Implementation of Electronic-Based Government Procurement of Goods and Services at the Department of Communications, Informatics, and Statistics of Wajo Regency - Syamsiar Syamsiar; Besse Herlina; Muhammad Nur; Tenri Dio (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the implementation of electronic-based government procurement of goods and services at the Department of Communications, Informatics, and Statistics of Wajo Regency and to identify the supporting and inhibiting factors affecting its implementation. A qualitative approach with a descriptive research design was employed. Data were collected through observation, interviews, and documentation involving the Head of Department, structural officials, implementing officers, and service providers. The findings indicate that the implementation of electronic procurement has generally been effective. Effective communication and coordination through socialization, meetings, and technical assistance have supported the procurement process. Adequate human resources and information technology infrastructure have facilitated the implementation of procurement through the Electronic Procurement System (SPSE). Furthermore, the commitment of implementers to comply with applicable regulations has enhanced transparency, efficiency, effectiveness, and accountability. The bureaucratic structure has functioned according to established duties and procedures while promoting information transparency through electronic systems. Supporting factors include strong coordination, competent personnel, adequate technological infrastructure, and transparent procurement information. However, implementation continues to face challenges, including internet network disruptions, technical issues in application systems, and the need to strengthen personnel capacity in adapting to evolving electronic procurement systems and regulations.